The Profile of Students' Critical Thinking Skills on Renewable Energy as Measured by a Scientific Literacy Instrument - Alifya Crystal Jasmine Zafira Zahra Budimansyah; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Inovasi Pendidikan Fisika, 2026)
Critical thinking skills need to be investigated because students must be able to analyze information, evaluate evidence, and make scientific decisions when dealing with increasingly complex energy issues. This study aims to describe high school students’ critical thinking skills profile on renewable energy as measured using a science literacy-based physics assessment instrument. This study employed a quantitative descriptive method involving 69 tenth-grade students at SMA IPIEMS Surabaya. The research instrument consisted of 20 essay items containing contextual renewable energy stimuli, such as articles, data tables, pictures, infographics, and socio-environmental cases. The items were developed based on five Facione critical thinking indicators, namely interpretation, analysis, evaluation, explanation, and inference, and were integrated with PISA science literacy competencies. The instrument met theoretical feasibility with an average validity of 94%, all items were empirically valid, and reliability was categorized as very high. The results showed that the mean critical thinking score was 70.41, categorized as high. A total of 27 students were in the very high category, 20 students were in the high category, 15 students were in the sufficient category, 5 students were in the low category, and 2 students were in the very low category. The analysis indicator obtained the highest mean score of 75.54, while the explanation indicator obtained the lowest mean score of 67.07. These findings indicate that students were relatively strong in identifying relationships among information, but still need reinforcement in constructing coherent, logical, and evidence-based scientific explanations. Theoretically, these results support the relationship between science literacy and critical thinking. Empirically, the science literacy-based instrument can be used to map students’ critical thinking skills profile on renewable energy topics.